Neuropsychiatric events in varenicline and nicotine replacement patch users in the Military Health System. (18th October 2012) - Meyer, Tamra E.; Taylor, Lockwood G.; Xie, Suji; Graham, David J.; Mosholder, Andrew D.; Williams, James R.; Moeny, David; Ouellet‐Hellstrom, Rita P.; Coster, Trinka S.
Abstract Aim To determine the rate ratio of neuropsychiatric hospitalizations in new users of varenicline compared to new users of nicotine replacement therapy (NRT) patch in the Military Health System (MHS). Design, setting and participants Varenicline (n = 19 933) and NRT patch (n = 15 867) users who initiated therapy from 1 August 2006 to 31 August 2007 within the MHS were included in this retrospective cohort study. After matching according to propensity scores, 10 814 users remained in each cohort. The study population included those with and without a history of neuropsychiatric disease. Measurements Patients were followed for neuropsychiatric hospitalizations defined by primary neuropsychiatric discharge diagnosis using ICD‐9 codes from in‐patient administrative claims. Hazard ratios (HR) and 95% confidence intervals (CI) were estimated after propensity score matching on exposure for socio‐demographic factors, health‐care utilization, comorbidities, medication history and neuropsychiatric history. Findings There was no increase in the rate of neuropsychiatric hospitalizations in patients treated with varenicline compared to NRT patch when followed for 30 days (propensity‐score matched HR = 1.14, 95% CI: 0.56–2.34). Results were similar after 60 days of follow‐up. Conclusions There does not appear to be an increase in neuropsychiatric hospitalizations with varenicline compared with nicotine replacement therapy patch over 30 or 60 days after drug initiation.